Drug Delivery Nanocarriers from a Fully Degradable PEG‐Conjugated Polyester with a Reduction‐Responsive Backbone. Issue 32 (14th July 2015) - Yameen, Basit; Vilos, Cristian; Choi, Won Il; Whyte, Andrew; Huang, Jining; Pollit, Lori; Farokhzad, Omid C.
Abstract: The remarkably high intracellular concentration of reducing agents is an excellent endogenous stimulus for designing nanocarriers programmed for intracellular delivery of therapeutic agents. However, despite their excellent biodegradability profiles, aliphatic polyesters that are fully degradable in response to the intracellular reducing environment are rare. Herein, a reduction‐responsive drug delivery nanocarrier derived from a linear polyester bearing disulfide bonds is reported. The reduction‐responsive polyester is synthesized via a convenient polycondensation process. After conjugation of terminal carboxylic acid groups of polyester to polyethylene glycol (PEG), the resulting polymer self‐assembles into nanoparticles that are capable of encapsulating dye and anticancer drug molecules. The reduction‐responsive nanoparticles display a fast payload release rate in response to the intracellular reducing environment, which translates into superior anticancer activity towards PC‐3 cells. Abstract : A reduction‐responsive drug delivery nanocarrier system derived from a linear polyester containing disulfide bonds in the main chain is reported. After conjugation to polyethylene glycol (PEG), the polymer self‐assembles into nanoparticles capable of encapsulating dyes and anticancer drugs. The nanoparticles are highly sensitive to the concentration of an intracellular reducing agent and exhibit superior anticancer activity.